World Bank and the Global Financing Facility. (31st August 2017) - Fernandes, Genevie; Sridhar, Devi
Abstract : In the fourth article of the series, Genevie Fernandes and Devi Sridhar describe the bank's new investment model for advancing reproductive, maternal, newborn, child, and adolescent health and nutrition